ANALISIS PENERAPAN POLITIK UANG PADA MASA DEMOKRASI DI KOTA SERANG PROVINSI BANTEN - Zahra, Maitza; Imelda, Maria; Ar-Rifdah, Nabila; Nurul, Reysha; Muhammad, Athhar (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The politics of money politic is not a foreign thing to be discovered. Many parts of Indonesia use the political lifeline of money during elections to attract people, as this article focuses on the city of attack, the province of banten. This is because of the poor quality of human resources and the weak economic growth in Indonesia. The politics of money also has many kinds so it can be distinguished according to its purposes and meanings. Politics of money also has differing meanings according to experts, so we examined the opinion of the experts in results and discussions